Solve for y -6*(9y)=14

Math
-6⋅(9y)=14
Multiply 9 by -6.
-54⋅y=14
Divide each term by -54 and simplify.
Tap for more steps…
Divide each term in -54⋅y=14 by -54.
-54⋅y-54=14-54
Cancel the common factor of -54.
Tap for more steps…
Cancel the common factor.
-54⋅y-54=14-54
Divide y by 1.
y=14-54
y=14-54
Simplify 14-54.
Tap for more steps…
Cancel the common factor of 14 and -54.
Tap for more steps…
Factor 2 out of 14.
y=2(7)-54
Cancel the common factors.
Tap for more steps…
Factor 2 out of -54.
y=2⋅72⋅-27
Cancel the common factor.
y=2⋅72⋅-27
Rewrite the expression.
y=7-27
y=7-27
y=7-27
Move the negative in front of the fraction.
y=-727
y=-727
y=-727
The result can be shown in multiple forms.
Exact Form:
y=-727
Decimal Form:
y=-0.259‾
Solve for y -6*(9y)=14

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top